Analysis of Factors Affecting Customer Satisfaction and Customer Loyalty in the Shopee Marketplace - Ringo, Rejhi Yunus Siringo; Septyanto, Dihin; Ramli, Abdul Haeba (Majalah Ilmiah Bijak, 2023)
This study aims to find out what factors influence customer satisfaction and loyalty in the Shopee marketplace. The variables used in this study are price, product quality, information quality, privacy issues, perceived security, product variety, delivery, customer satisfaction and customer loyalty. The population in this study are marketplace users who have used and shopped at the Shopee marketplace with a sample size of 180 respondents. The data collection technique used a questionnaire, and the data analysis technique used was the SmartPLS 4.0 analysis tool. Based on the research results, of the 15 hypotheses there are 9 hypotheses that are accepted, namely information quality, perceived security, privacy issues, delivery and product variety have a positive effect on customer satisfaction and loyalty. Perceived security, information quality, privacy issues, and product delivery have a positive effect on customer loyalty through customer satisfaction. The contribution to this research resulted in a model for measuring the effectiveness of the Shopee marketplace system that companies can use to develop in the future so as to increase user satisfaction at Shopee.